The associations between calorie tracking, body image dissatisfaction, eating disorders, and menstrual cycle characteristics in resistance-trained athletes - Kimberly SantaBarbara; Eric Helms; Nigel Harris (Taylor & Francis Group, 2024)
Background While body image dissatisfaction (BID) and eating disorders (EDs) are relatively common in athletes (ranging from 11% to 67% of athletes, depending on the sport) [1], they are also prevalent in weight-class restricted sports (a common format in strength sports), and among physique athletes [2]. These athletes manipulate their nutrition to reach aesthetic or body weight standards and, in that process, may undergo prolonged periods of low energy availability. Low energy availability, defined as consuming insufficient energy for one's lean mass and exercise activity, can lead to Relative Energy Deficiency in sport (REDs), a syndrome that can impact menstrual cycle (MC) symptoms (and many other aspects of physiology and psychology) [3]. There has not been an investigation into the relationships between these resistance-trained (RT) athletes' nutritional habits, MC-related symptoms, BIDs, and EDs.Methods A survey was implemented to explore the dieting habits, MC characteristics, BID, and EDs in RT females.Results 64.6% (n = 469) of participants reported tracking calories, with a slightly higher percentage of competitive athletes tracking calories 71.8% (n = 181) than recreational-level athletes. Competitive athletes were significantly more likely to track calories than recreational-level athletes (p = 0.003). When asked what the primary purpose of calorie restriction was, most participants selected weight loss for aesthetic purposes 58.8% (n = 356). Competitive athletes were less likely to select weight loss for aesthetic purposes 35.7% (n = 77), but weight loss for the purpose of a weight class-based sport was higher at 43.5% (n = 94). There were no significant associations between BID and MC characteristics or most MC symptoms and limited associations between EDs and MC characteristics and symptoms.Conclusion RT athletes exhibited a higher prevalence of calorie tracking than the general population. Competitive RT athletes were less likely to calorie restrict for aesthetic purposes than non-athletes, but more likely to calorie restrict for the purpose of weight-class-based sports. There were limited significant associations between BID and MC characteristics or MC symptoms, as well as between EDs and MC characteristics. However, there was a significant association between amenorrhea and EDs, which aligns with previous research in this area. Both BID and EDs were significantly associated with MC-based mental health effects; this is likely due to the interconnected nature of mental health concerns, such as EDs with depression and anxiety.